2017
DOI: 10.3389/fped.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Full Spectrum of Organ Injury Following Intrapartum Asphyxia

Abstract: Birth asphyxia is a significant global health problem, responsible for ~1.2 million neonatal deaths each year worldwide. Those who survive often suffer from a range of health issues including brain damage—manifesting as cerebral palsy (CP)—respiratory insufficiency, cardiovascular collapse, and renal dysfunction, to name a few. Although the majority of research is directed toward reducing the brain injury that results from intrapartum birth asphyxia, the multi-organ injury observed in surviving neonates is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 141 publications
(185 reference statements)
0
39
0
1
Order By: Relevance
“…Severe and prolonged asphyxia can result in either intrauterine fetal death and stillbirth or multiorgan failure in surviving neonates (2). Peripartum and intrapartum ischemic or hypoxic insults are, in many cases, impossible to anticipate and may be difficult to recognize before the delivery of the baby.…”
Section: Perinatal Asphyxiamentioning
confidence: 99%
See 3 more Smart Citations
“…Severe and prolonged asphyxia can result in either intrauterine fetal death and stillbirth or multiorgan failure in surviving neonates (2). Peripartum and intrapartum ischemic or hypoxic insults are, in many cases, impossible to anticipate and may be difficult to recognize before the delivery of the baby.…”
Section: Perinatal Asphyxiamentioning
confidence: 99%
“…Creatine is considered to be a worthy contender as a good source of energy in the context of PA. It can serve as energy supply not only for the brain but for the myocardium as well (2,109). Multiple experimental studies using maternal diet supplementation with creatine show positive results, mainly on the diaphragm, but recent data indicate cardioprotective effects through HIF-1 activation (110).…”
Section: Creatinementioning
confidence: 99%
See 2 more Smart Citations
“…In the neonatal brain HI triggers a cascade of biological processes culminating in cell death (Griva et al, 2017; Sukhanova et al, 2016). Studies of the development of HI brain damage in animal models have shown that oxidative stress plays an important role in causing organ injury in the compromised fetus and neonate (LaRosa et al, 2017; Millar et al, 2017). The immature brain is known to be particularly susceptible to oxidative stress‐mediated ischemia/reperfusion injury compared to the mature brain.…”
Section: Introductionmentioning
confidence: 99%